Two rarities together: A free peritoneal body in a hernia en pantaloon sac and case series of our experience of finding loose peritoneal bodies (Indian Journal of Case Reports, 2019)
Peritoneal loose bodies (PLBs) are rare findings that were reported extensively in the early nineteenth and twentieth century in the form of case series by Littre, Riedel and Macintosh. In the recent past, focus has shifted more towards symptomatic free peritoneal bodies. Although a proper intrabdominal examination and histopathology can help to clear the diagnosis, there is still no consensus in the surgical circle as to how to deal with them. Here, we report a case series of 4 cases of finding loose peritoneal bodies during intra-abdominal procedures, three of them were found during laparoscopic procedures (laparoscopic appendectomy, Robotic mesh rectopexy and laparoscopic bowel resection) while one was an open surgery (open inguinal hernia repair). This paper is unique as for the first time in the history it brings two surgical rarities together i.e. ‘hernia en pantaloon’ and free peritoneal body along with recommendations based on the literature, review to diagnose and treat loose peritoneal bodies.